Situation Report: Baltic Area, 21 April 1989 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. A Victory for the Reformers in Estonia and Latvia / by Dzintra Bungs Unofficial Groups in the Baltic Republics an Access to the Mass Media / by Saulius Girnius Lutherans on a Reform Course / by Dzintra Bungs Sajudis Candidates Sweep Elections / by Dzintra Bungs Preliminary Results of Run-off Elections / by Saulius Girnius The Lithuanian Communist Party in a Quandary / by Kestutis Girnius